Analisis Karakteristik Bunyi Dalam Percobaan Sederhana - Mulia Hayati; Siska Mulia; Sri Wulandari (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research aims to analyze the basic characteristics of simple experiment. The main focus is to observe and measure sound properties such as frequency, amplitude, and speed of propagation under various conditions. The experiments include the use of a tuning fork to determine frequency and resonance in an air column to calculate the speed of sound in air. Additionally, changes in sound intensity are observed along with changes in distance from the sound source. The results of the experiments show a direct relationship between the length of the resonant air column and the wavelength of sound, as well as an inverse relationship between sound intensity and the squae of distance. This research reinforces basic physics principles about sound waves, providing a clear understanding of the fundamental properties of sound through easily replicable experimental methods.